FACTORES QUE INFLUYEN EN LA ACEPTACIÓN DEL USO DE MÉTODOS ANTICONCEPTIVOS EN PUÉRPERAS DEL HOSPITAL SAN JOSE DE CHINCHA, DURANTE EL PERIODO DE SETIEMBRE A DICIEMBRE DEL 2019 - RONCEROS CÁRDENAS, LUZ NORIELY (2020)
OBJECTIVE: “To determine the factors that influence the acceptance of the use of contraceptive methods in puerperal women at the Hospital San José of Chincha during the period from September to December 2019”. METHODS AND TECHNIQUES: Quantitative method study, prospective cross-sectional, non-experimental. Population made up of 366 postpartum women, with a sample of 186 postpartum women. Technique employed was through a survey previously validated by expert judges, and was carried out with the SPSS V25.0 program. RESULTS: 55.9% of the postpartum women were between 13 and 25 years old, 63.3% were Catholic, 70.7% were housewives, 63.8% were cohabitants, and the predominant educational level was secondary with 58%. Spousal acceptance for contraceptive use was found to be 93.6%, with interference from a family member being only 5.3%. The level of knowledge was low (51.6%), and it was found that knowledge is statistically related to acceptance with a p value of 0.001*, with favourable beliefs at 53.7%. In addition, it was shown that anemia was a predisposing factor in the acceptance of the use of some contraceptive method. 74.5% of postpartum women opted for the use of MAC, with the quarterly injectable having better acceptance (37.8%). CONCLUSION: It was concluded that there are still barriers that influence the acceptance of MAC, being the most predominant the cognitive factors, happening that the puerperas leave of discharge without using some contraceptive method, predisposing again to a pregnancy with short intergenesic period. Keywords: Contraceptive method, puerperium, factors (DeCS BIREME)